Comparison of the amount of marginal fit and shear strength tolerance between the prefabricated abutments and the abutments manufactured using the CAD/CAM method of zirconia and the abutments manufactured by the waxing method of the chroum-cobalt mixture (Latakia University Journal -Medical Sciences Series, 2023)
Aim of the study: this study aimed to compare the marginal fit accuracy and fatigue resistance between stock abutments, milled zirconia abutments, and lost wax chrome-cobalt abutments.Materials and methods: An in vitro study was conducted on 30 abutments, divided according to manufacturer method into three equal groups (ten stock abutments, ten milled zirconia abutments, and ten lost wax chrome-cobalt abutments). The marginal fit accuracy and the fatigue resistance tests were done for three groups, and the values were registered. One way Anova was used to compare the means between the three studied groups and Tukey tests were used as a post-hoc test.Results: A statistically significant difference was found when comparing the marginal fit accuracy between the three groups (p